FEMALE GENITAL MUTILATION - FORENSIC MEDICAL INTERPRETATION UNDER THE CRIMINAL CODE OF THE REPUBLIC OF BULGARIA. PRESENTATION OF TWO CASES - Alexandar Alexandrov; Mihaela Georgieva; Teodora Kiryakova; Atanas Hristov; Ivan Tsranchev; Pavel Timonov (Science & Research)

(untitled)
Female genital mutilation (FGM) is the ritual cutting of some or all of the external female genitalia, practiced mainly in countries in Africa, Asia and the Middle East. We present two cases of women, respectively 27 years old and 35 years old, sought asylum in the Republic of Bulgaria as migrants from different African countries, and one of them had two normal pregnancies and, respectively, two births of healthy children. The two women reported that at different periods of their childhood (at the age of 7 and 14, respectively) they had been "circumcised" against their will by "specialists" (elderly women), without anesthesia and prior disinfection of the "operative field", they were immobilized by four or five men, each holding one of their limbs and one sitting on the abdomen. The procedures were performed with a "razor" or model knife, respectively. In both cases there were clinically manifested with bleeding, secretions and subsequent infections from the surgical wounds. To overcome these consequences they used for a long period bandages and performed cleansing the areas with local herbal decoctions (in violation of the basic principles of asepsis and antiseptics). Both patients reported that the healing processes of this "operative" procedure and the subsequent "treatment" lasted an extremely long time (one of them said that such inflammatory changes in the area of the operative scar often occur in the last year). In addition, they confessed that they have never in their lives experienced any sexual pleasure, but on the contrary have experienced pain in most of their sexual intercourse. The forensic examination of both females revealed a complete lack of glans and / or partial or complete absence of the clitoral body. In their proper areas, an old scar was observed, taking into account the presence of pain in both patients that occurred when stretching the labia, as well as during palpation in the area of the established scar. Thanks to governmental and non-governmental national and international organizations, programs have been established since the middle of the last century to stop or reduce the spread of FGM. Clauses prohibiting this practice are included in a large number of international legal instruments and in the legislation of many countries around the world.